O estudo dos metaplasmos do português moderno: uma aplicação no contexto das redes sociais - ARAÚJO, Amanda Gonçalves de (2022)
The language lives in constant processes of change, day after day new words appear and bring innovations to the language, in Portuguese this is no different. Therefore, this work entitled “The Portuguese Metaplasms of the modern portuguese: an application on the context of the social networks” focuses on analyzing the publications found on social networks, to verify how the metaplasm process is seen as linguistic. The theoretical foundation of this research was based on the Coutinho (1976), Mattoso (1979), Botelho (undated), Houaiss (2021), Mollica (2004), Bagno (1999) and Possenti (1996), studies.